Strategic analysis of innovation processes in higher education institutions: A mixed-method approach to environmental - Verens Elvira; Retno Kusumastuti (Journal of Environment and Geography Education, 2025)
Background: Innovation is a crucial driver for higher education institutions to enhance competitiveness and academic excellence. Universitas Indonesia (UI) has implemented various innovation strategies, but the effectiveness and challenges of these processes require further investigation. This study aims to analyze the driving and inhibiting factors in UI’s innovation processes and formulate strategic recommendations to optimize institutional innovation. Methods: This study employs a mixed-method approach, combining quantitative and qualitative analyses. The quantitative analysis uses descriptive statistics with Statistical Product and Service Solution (SPSS) to examine data distribution and categorize responses into high, moderate, and low classifications. Meanwhile, the qualitative analysis is based on in-depth interviews, where data is processed using coding techniques (open coding, axial coding, and selective coding) to identify key themes. The analysis follows the structured methodology proposed by Daymon & Holloway (2010), consisting of data reduction, organization, coding, interpretation, and evaluation. Findings: The conclusion of this study shows that innovation at the Universitas Indonesia is influenced by the strategies implemented and various supporting and inhibiting factors. Quantitative analysis reveals that institutional support, academic collaboration, and technology utilization significantly contribute to the success of innovation at UI. The majority of respondents have a positive perception of the innovation strategies implemented, as indicated in the categorization of the average value. Meanwhile, qualitative analysis through in-depth interviews identified major obstacles to innovation, including bureaucratic complexity, limited funding, and resistance to change. Conclusion: Innovation at the University of Indonesia is influenced by institutional and technological support, but faces challenges of bureaucracy, funding, and resistance to change. Novelty/Originality of this article: This study analyzes the innovation process in higher education through mixed methods, revealing the strategic factors that play a role in UI. The results provide new insights and policy recommendations to improve ecosystem innovation.